Is there a relation between inflow of direct foreign investments and economic growth of European Union states? - Stawicka, Magdalena (Publishing House of the Wrocław University of Economics, 2009)
The situation in the world shows that nearly all states of the world affect each other while functioning of one of them is conditioned by operations of other states. This mutual affection and relations between states were started at the moment when first economies suffering from lack of resources were forced to look for them in other states. Consequently, it resulted in share of domestic and international economic problems. The feature of the contemporary world is unquestionable occurrence of series of interactions and relations between states. In recent years these phenomena have noticeably increased. So the awareness of their existence must grow up and, therefore, a conviction that they must be taken into consideration within a process of making decisions. The above-mentioned relations connected with resources and ways of obtaining them in the situation, when one state suffered from lack of resources while in the other one there were too much resources, in the 19th century have been extended by a new element, namely, a will to obtain a higher profit rate than on domestic market. Moreover, during this period there appeared a serious increase in industrial production in Western Europe states, which made exporters, who wanted to ensure an access to foreign resources, invest their capital abroad in form of foreign investments. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 417-424